Analisis Persepsi Pondok Pesantren Terhadap Lembaga Keuangan Syariah (Studi Kasus Pada Pondok Pesantren Zainul Hasan Genggong Probolinggo) - Mustofa Mustofa; Zainollah Zainollah (RELASI : JURNAL EKONOMI, 2018)
The existence of sharia financial institutions in the districts Probolinggo became the object of interest primarily among boarding school. Islamic financial institutions conducted by the banking community has created a separate perception for the community of pesantren or santri . The activities of Islamic financial institutions be interesting people, but the existence of the financial institution of sharia cause different perceptions. Some assume that Islamic financial institutions are no different from conventional financial institutions. The research method used is qualitative descriptive analysis. Collected by observation technique and interview with structured question supported by closed questionnaire to informant to know opinion perception of the existence of Islamic financial institutions , by using Snowball Sampling method. From the discussion of the above problems, it can be concluded that the perception of the santri community at the Genggong cottage, both those who are customers and those who are not Islamic bank customers, in terms of cultural, social, personal and psychological approaches, is positive towards Islamic banks. The differences that exist in the santri community of customers and non customers are on their attitude or choice to choose or not to choose sharia bank. Keywords: Islamic finance, santri , pesantren